The UK equity market around the ex-split date - Kalotychou, Elena; Staikouras, Sotiris K.; Zagonov, Maxim (My University, 2009)
Using UK stock market data this study unveils positive abnormal returns on and around the ex-split date. These excess returns are partially predictable using the publicly available information prior to the ex-split date. There is also a persistent increase in the post-split volatility of these stocks with the results being robust to the choice of the volatility proxy. Post-split volatility is found to be positively related to trading activity. Contrary to the US findings, volatility dynamics following the stock split are better captured by changes in the daily trading volume rather than by the number of trades.
Keywords: Equity abnormal returns; Ex-split date; Stock market volatility; Stock splits